Probiosis: concepts and prospects - Barbosa, Lima R(Universidade Federal da Paraíba Centro de Ciências Agrárias Departamento de Zootecnia); Figueiredo-Lima, DF(Universidade Federal Rural de Pernambuco Unidade Acadêmica de Garanhuns); Givisiez, PEN(Universidade Federal da Paraíba Centro de Ciências Agrárias Departamento de Zootecnia); Rabello, CBV(Universidade Federal Rural de Pernambuco); Gonzales, E(Universidade Estadual Paulista Júlio de Mesquita Filho Faculdade de Medicina Veterinária e Zootecnia); Silva, JHV(Universidade Federal da Paraíba Centro de Formação de Tecnólogos) (Revista brasileira de ciência avícola, 2010)
The use of probiotics in animal and human feeding has been a subject of increasing interest both for the academia and the industry, mostly due to their potential positive effects on health and profitability. However, the knowledge on the composition of bacterial gastrointestinal communities in humans and animals, as well as its respective nutritional requirements, is far from being elucidated. Due to the ban of the use of antibiotic growth promoters in animal feeds, there has been an increasing interest on the utilization of probiotics to improve animal intestinal health under commercial settings. However, the possibility of horizontal transference of antibiotic-resistant genes between probiotic bacteria and pathogenic species has become a concern of poultry farmers and consumers around the world. Innovative ideas have emerged, such as the addition of essential oils, spices, and other plant extracts to feeds of monogastric animals to promote intestinal health. These natural compounds are considered ecologically adequate and safe for feeding purposes. This new reality will probably change the direction of research and of the use of additives in poultry production.